Hilary of Poitiers : conflicts of conscience and law in the fourth-century church : "Against Valens and Ursacius" : the extant fragments, together with his "Letter to the emperor Constantius" - Hilarius, svatý, asi 315-367 (Translated texts for historians ;, 1997)
Two texts are presented in English translation here. The first is what remains of a historical work Hilary wrote against two distinguished contemporary bishops, Valens and Ursacius, whose intervention on behalf of the Emperor Constantius Hilary thought disastrous. They throw a flood of light upon scenes of disarray, violence and betrayal in the Church life of the fourth century.